Employee Job Satisfaction at SMEs: Kepuasan Kerja Karyawan pada UMKM - Wahyu Aji Putra; Widyastuti (Universitas Muhammadiyah Sidoarjo, 2022)
This study is intended to explain how job satisfaction on UD Bumbu Masak Machmudah, Sidoarjo. In this research, the writer uses descriptive quantitative method using a single variable. The number of samples in this study were 135 respondents. The respondents in this study were all UD. Bumbu Masak Machmudah The sampling technique in this study used a saturated sampling technique to obtain research data. In collecting data, the authors distributed questionnaires to respondents and also interviews. In proving and analyzing this, validity and reliability tests, descriptive tests, and Crosstabs tests are used. The test results show that 17.8% of which 24 employees prove that employee job satisfaction is high, and the highest aspect of job satisfaction is the compensation aspect, which is 15.2%. And there is no difference between the job satisfaction of male and female employees and there is a difference between job satisfaction for employees with elementary, middle, and high school graduates. Highlights: The study focuses on job satisfaction in UD Bumbu Masak Machmudah, Sidoarjo, using a descriptive quantitative method with a single variable. A sample size of 135 respondents was chosen through saturated sampling, and data was collected through questionnaires and interviews. The test results indicate that 17.8% of employees have high job satisfaction, with the compensation aspect being the most significant. There is no gender difference in job satisfaction, but differences are observed based on educational background. Keywords: job satisfaction, UD Bumbu Masak Machmudah, descriptive quantitative method, sample size, compensation aspect.